Tell Me the Story of How I Conquered You : Elsewheres and Ethnosuicide in the Colonial Mesoamerican World - Rabasa, Jose (Book collections on Project MUSE., 2011)
Applying contemporary intellectual perspectives, including aspects of gender, modernity, nation, and visual representation itself, Jose Rabasa reveals new perspectives on colonial order. Folio 46r becomes a metaphor for reading the totality of the codex and for reflecting on the postcolonial theoretical issues now brought to bear on the past. Ambitious and innovative (such as the invention of the concepts of elsewhere and ethnosuicide, and the emphasis on intution), Tell Me the Story of Howl Conquered You embraces the performative force of the native scribe while acknowledging the ineffable traits of 46r-traits that remain untenably foreign to the modern excavator/scholar. Posing provocative questions about the unspoken dialogues between evangelizing friars and their spiritual conquests, this book offers a theoretic-political experiment on the possibility of learning from the tlacuilo ways of seeing the world that dislocate the predominance of the West.